Analisis Produktivitas Tenaga Kerja Pada Pekerjaan Atap Pada Pembangunan Sekolah Dasar Al-Azhar Summarecon Mutiara Makassar - Oktiarayfika (Paulus Civil Engineering Journal, 2025)
The success of a construction project heavily depends on the availability and role of labor. In its implementation, labor productivity capacity is crucial to achieving optimal results. In the construction of Al-Azhar Summarecon Mutiara Makassar Elementary School, a study was conducted aimed at analyzing labor productivity, particularly in the installation of wide flange steel roof trusses. This research was carried out through direct field observations to measure labor productivity, which was then compared with the SNI 7393:2008 standard. Based on the analysis, the average productivity of workers in the installation of wide flange steel roof trusses was found to be 99.34 kg/man-hour. Meanwhile, the productivity according to SNI standards for the installation of wide flange steel roof trusses is 166.6 kg/man-hour. This indicates that the labor employed in the process of installing wide flange steel roof trusses is not productive.